Characterization of Various Environmental Influences on the Inductive Localization - Lange, Sven; Hilleringmann, Ulrich; Hedayat, Christian; Kuhn, Harald; Förstner, Jens (2023 IEEE Conference on Antenna Measurements and Applications (CAMA))
In this paper, the influence of the environment on an inductive location system is analyzed. In the inductive location method, high frequency magnetic fields generated by planar coils lead to induction in other coils, which is used for localization analysis. Magnetic fields are not affected by changes in the dielectric properties of the environment, which is an advantage over other localization methods. However, electrical material parameters can still affect the localization results by indirect effects. For this reason, in this publication the influence will be investigated using real material parameters and their effects on the localization will be considered, so that the robustness and the limits of the inductive localization can be evaluated.
Keywords: Planar coils; inductive locating; magnetic fields; environmental influences; eddy currents; tet_topic_hf

On‐Demand Indistinguishable and Entangled Photons Using Tailored Cavity Designs - Bauch, David; Siebert, Dustin; Jöns, Klaus; Förstner, Jens; Schumacher, Stefan (Advanced Quantum Technologies)
Abstract The biexciton‐exciton emission cascade commonly used in quantum‐dot systems to generate polarization entanglement yields photons with intrinsically limited indistinguishability. In the present work, it focuses on the generation of pairs of photons with high degrees of polarization entanglement and simultaneously high indistinguishability. It achieves this goal by selectively reducing the biexciton lifetime with an optical resonator. It demonstrates that a suitably tailored circular Bragg reflector fulfills the requirements of sufficient selective Purcell enhancement of biexciton emission paired with spectrally broad photon extraction and twofold degenerate optical modes. The in‐depth theoretical study combines (i) the optimization of realistic photonic structures solving Maxwell's equations from which model parameters are extracted as input for (ii) microscopic simulations of quantum‐dot cavity excitation dynamics with full access to photon properties. It reports non‐trivial dependencies on system parameters and use the predictive power of the combined theoretical approach to determine the optimal range of Purcell enhancement that maximizes indistinguishability and entanglement to near unity values, here specifically for the telecom C‐band at 1550 nm.
Keywords: tet_topic_qd

On-demand indistinguishable and entangled photons at telecom frequencies using tailored cavity designs - Bauch, David; Siebert, Dustin; Jöns, Klaus; Förstner, Jens; Schumacher, Stefan
The biexciton-exciton emission cascade commonly used in quantum-dot systems to generate polarization entanglement yields photons with intrinsically limited indistinguishability. In the present work we focus on the generation of pairs of photons with high degrees of polarization entanglement and simultaneously high indistinguishibility. We achieve this goal by selectively reducing the biexciton lifetime with an optical resonator. We demonstrate that a suitably tailored circular Bragg reflector fulfills the requirements of sufficient selective Purcell enhancement of biexciton emission paired with spectrally broad photon extraction and two-fold degenerate optical modes. Our in-depth theoretical study combines (i) the optimization of realistic photonic structures solving Maxwell's equations from which model parameters are extracted as input for (ii) microscopic simulations of quantum-dot cavity excitation dynamics with full access to photon properties. We report non-trivial dependencies on system parameters and use the predictive power of our combined theoretical approach to determine the optimal range of Purcell enhancement that maximizes indistinguishability and entanglement to near unity values in the telecom C-band at $1550\,nm$.
Keywords: tet_topic_phc; tet_topic_qd

The effectiveness of vaccination, testing, and lockdown strategies against COVID-19 - Fritz, Marlon; Gries, Thomas; Redlin, Margarete (International Journal of Health Economics and Management)
Abstract The ability of various policy activities to reduce the reproduction rate of the COVID-19 disease is widely discussed. Using a stringency index that comprises a variety of lockdown levels, such as school and workplace closures, we analyze the effectiveness of government restrictions. At the same time, we investigate the capacity of a range of lockdown measures to lower the reproduction rate by considering vaccination rates and testing strategies. By including all three components in an SIR (Susceptible, Infected, Recovery) model, we show that a general and comprehensive test strategy is instrumental in reducing the spread of COVID-19. The empirical study demonstrates that testing and isolation represent a highly effective and preferable approach towards overcoming the pandemic, in particular until vaccination rates have risen to the point of herd immunity.
Keywords: Health Policy; Economics; Econometrics and Finance (miscellaneous)

Émile Durkheim: Father of the Sociology of Education - Lin-Januszewski, Liang-Wen (The Palgrave Handbook of Educational Thinkers)

Bolzano, Bernard: Briefe an Michael Josef Fesl 1837–1840. hg. v. Otto Neumaier, Frommann-Holzboog, Eckhart Holzboog: Stuttgart-Bad Cannstatt 2022 (Bernard Bolzano-Gesamtausgabe. Reihe III: Briefwechsel. Bd. 2.3) - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete Zbl 1512.01036)

Wolfram, Stephen. Dropping in on Gottfried Leibniz. In: Unravelling Complexity: The Life and Work of Gregory Chaitin, hg. v. Francisco Antonio Doria und Shyam Wuppuluri, World Scientific: Hackensack, NJ 2020, 49–81 - Peckhaus, Volker (Mathematical Reviews MR4450759)

Bolzano, Bernard. Briefe an Michael Josef Fesl 1841–1845. hg. v. Otto Neumaier, Frommann-Holzboog, Eckhart Holzboog: Stuttgart-Bad Cannstatt 2022 (Bernard Bolzano-Gesamtausgabe. Reihe III: Briefwechsel. Bd. 2.4). - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete ZBl 1512.01037)

Wolfgang Tschirk: Vom Universum des Denkens. Eine Geistesgeschichte der Logik. Springer: Berlin 2022 - Peckhaus, Volker (Mathematische Semesterberichte)

Softsensors: key component of property control in forming technology - Homberg, Werner; Arian, Bahman; Arne, Viktor; Borgert, Thomas; Brosius, Alexander; Groche, Peter; Hartmann, Christoph; Kersting, Lukas; Laue, Robert; Martschin, Juri; Meurer, Thomas; Spies, Daniel; et al. (Production Engineering)
Abstract The constantly increasing challenges of production technology for the economic and resource-saving production of metallic workpieces require, among other things, the optimisation of existing processes. Forming technology, which is confronted with new challenges regarding the quality of the workpieces, must also organise the individual processes more efficiently and at the same time more reliably in order to be able to guarantee good workpiece quality and at the same time to be able to produce economically. One way to meet these challenges is to carry out the forming processes in closed-loop control systems using softsensors. Despite the many potential applications of softsensors in the field of forming technology, there is still no definition of the term softsensor. This publication therefore proposes a definition of the softsensor based on the definition of a sensor and the distinction from the observer, which on the one hand is intended to stimulate scientific discourse and on the other hand is also intended to form the basis for further scientific work. Based on this definition, a wide variety of highly topical application examples of various softsensors in the field of forming technology are given.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

Die schriftbildliche Gestaltung von lexikalisch übernommenen Markennamen. Ein explorativer Wahrnehmungstest zum graduellen Entrenchment von Markennamen als multimodale Konstruktionen - Dübbert, Alexander (Beiträge zur Namenforschung)
Dieser Beitrag untersucht, inwiefern sich die kognitive Verankerung von der schriftbildlichen Gestaltung lexikalisch übernommener Markennamen nachweisen lässt. Dazu werden die Ergebnisse eines tachistoskopischen Wahrnehmungstests ausgewertet, bei dem einer Testgruppe die Schriftbilder (Logos) der Markennamen 'FÜR', 'Landliebe', 'MONSTER', 'GUT & GÜNSTIG', 'kinder' und 'ja!' mehrmals für Sekundenbruchteile (0,01s, 0,02s, 0,1s und 1,0s) und teils mit substituiertem Schriftzug präsentiert wurden. Insgesamt deutet die explorative Untersuchung – mit graduellen Abweichungen – in die Richtung, dass die Wahrnehmung des Schriftbilds zum Erkennen des dazugehörigen Markennamens führt. Dies ermöglicht die Schlussfolgerung, dass sich die getesteten Markennamen als multimodale Konstruktionen mit konstitutiver Schriftbildlichkeit qualifizieren.

Zwischen Überwältigung und Beliebigkeit - Wertorientierung im Unterricht als Aufgabe der Lehrpersonenbildung - Schlegel-Matthies, Kirsten (Nachdenken über Lehrerinnen- und Lehrerbildung. Anregungen zur Weiterentwicklung der Pädagogischen Hochschulen in der deutschsprachigen Schweiz. Aus Anlass des 20-Jahre-Jubiläums der Pädagogischen Hochschule Luzern)

Open Research Practices and Cultural Change: A Commentary on “(Why) Are Open Research Practices the Future for the Study of Language Learning?” - Steinhardt, Isabel; Mauermeister, Sylvi; Schmidt, Rebecca (Language Learning)
Keywords: Open Science; Open Science Practices; Cultural Change

Teacher's roles and teacher professionalism - Lin-Januszewski, Liang-Wen (Sociology of education: Theory, experience and implication)

The Bot Delusion. ChatGPT and anticipated consequences for research communication - Wieczorek, Oliver; Steinhardt, Isabel; Schneijderberg, Christian; Schmidt, Rebecca; Mauermeister, Sylvi
The reproduction of social inequalities through artificial intelligence (AI) and machine learning via artificial neural networks (ANN) has been demonstrated empirically in various areas of society, for instance in policing and personnel hiring decisions. Yet, a broader discussion is missing to what extent ANN technological developments may affect the scientific enterprise and reinforce or mitigate existing structural inequalities in academia. Focusing on publications and citations as main currencies in science, the anticipated consequences of ChatGPT on the research communication of existing and new knowledges are discussed in three scenarios, which echo the social structures in academia.

Die Rechtfertigung des Kapitalismus und die Kritik. Der neue Geist des Kapitalismus von Luc Boltanski und Ève Chiapello - Knoll, Lisa (Soziologische Gegenwartsdiagnosen 3)

Similar Affordances, Different Use Practices? An Investigation of Socio-Cultural Contexts in Facebook, Instagram and Twitter - Arslan, Kader; Trier, Matthias (Proceedings of the 44th International Conference on Information Systems (ICIS 2023))

Discrete Lagrangian Neural Networks with Automatic Symmetry Discovery - Lishkova, Yana; Scherer, Paul; Ridderbusch, Steffen; Jamnik, Mateja; Liò, Pietro; Ober-Blöbaum, Sina; Offen, Christian (IFAC-PapersOnLine)
By one of the most fundamental principles in physics, a dynamical system will exhibit those motions which extremise an action functional. This leads to the formation of the Euler-Lagrange equations, which serve as a model of how the system will behave in time. If the dynamics exhibit additional symmetries, then the motion fulfils additional conservation laws, such as conservation of energy (time invariance), momentum (translation invariance), or angular momentum (rotational invariance). To learn a system representation, one could learn the discrete Euler-Lagrange equations, or alternatively, learn the discrete Lagrangian function Ld which defines them. Based on ideas from Lie group theory, in this work we introduce a framework to learn a discrete Lagrangian along with its symmetry group from discrete observations of motions and, therefore, identify conserved quantities. The learning process does not restrict the form of the Lagrangian, does not require velocity or momentum observations or predictions and incorporates a cost term which safeguards against unwanted solutions and against potential numerical issues in forward simulations. The learnt discrete quantities are related to their continuous analogues using variational backward error analysis and numerical results demonstrate the improvement such models can have both qualitatively and quantitatively even in the presence of noise.

Ernst Schröder’s Algebra of Logic and the ‘Logic of the Ancient - Peckhaus, Volker (Aristotle’s Syllogism and the Creation of Modern Logic: Between Tradition and Innovation, 1820s–1930s (Bloomsbury Studies in the Aristotelian Tradition))

Nakano, Anderson: On Ramsey’s Reason to Amend Principia Mathematica’s Logicism and Wittgenstein’s Reaction, Synthese 199 (2021), 2629–2646. - Peckhaus, Volker (Mathematical Reviews MR4341825)